Bronchiectasis in the setting of aplasia of the epiglottis - Puwakdandawe Weerasinghe (Respirology Case Reports, 2019)
Aplasia of the epiglottis is a rare airway abnormality requiring airway and feeding interventions. We report a case of bronchiectasis in the setting of congenital aplasia of the epiglottis, secondary to early‐life aspiration events. Compensatory mechanisms for airway protection likely develop later in life.